A bio-based phosphorus-containing co-curing agent towards excellent flame retardance and mechanical properties of epoxy resin. (May 2021) - Cao, Jianfan; Duan, Huajun; Zou, Jiahao; Zhang, Junjun; Ma, Huiru
Highlights: A bio-based phosphorus-containing flame retardant VFD was synthesized. The addition of VFD accelerated the crosslinking reaction of epoxy system. VFD greatly improved the flame retardance and mechanical properties of EP. Abstract: To cater for the requirement of environmental protection, flame retardance and mechanical properties in some special fields for epoxy resin, a bio-based reactive flame retardant (VFD) derived from vanillin, furfurylamine and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) was successfully synthesized via one-pot method, and served as co-curing agent of DDM to prepare the flame-retardant EP. The structure of VFD was characterized by Fourier transform infrared (FTIR) spectra and nuclear magnetic resonance (NMR). The addition of VFD accelerated the crosslinking reaction of epoxy system and improved the flame retardance of EP. With VFD content was 7.5 wt% (only 0.52 wt% phosphorus was loaded), EP/VFD-7.5 achieved vertical burning (UL-94) V-0 rating and its limited oxygen index (LOI) value increased to 34.5%. Besides, compared with EP, the peak heat release rate (PHRR) of EP/VFD-7.5 decreased by 28% in cone calorimeter (CC) test. The analysis of char residue and pyrolysis behavior confirmed that VFD exerted bi-phase flame-retardant effect. In spite of the decrease of flame-retardant EPs' Tg, the tensile and flexural strengths of EP/VFD-10 increased by 45% and 29%, respectively. All the results indicated the great potential of VFD for practical application in future.